04 FAKTOR-FAKTOR YANG MEMPENGARUHI PENAWARAN JAGUNG DI SULAWESI SELATAN - Jurnal Agribis; Nurhudayah Nurhudayah; Arifin Arifin; Mohammad Anwar Sadat (Universitas Muslim Maros, 2018)
The purpose of this research is to find factors that influences offer corn in South Sulawesi Province with using the production variables (X1), the price of corn (X2) and price of rice (X3) and to know variable dominant that influence the offer corn in South Sulawesi Province. The data used in this research was secondary data from year 2000-2015 which includes data production, the price of corn, and price of rice. Secondary data is obtained from the central bureau of statistics South Sulawesi. The method of analysis the data used was linear regression multiple. The research results show factors that the affect is the price of corn and widely distributed family corn harvest in to the comparison. The behavior of the acreage of a corn on the region of the development of more influenced by the fact that the level of fluctuations in the price of corn he who puts his trust, while in the case of the region of which are the centers of more influenced by the size of the previous year harvest in to the comparison. The opposite has happened on conduct productivity of low class corn where a modifier key ones of which are this had an impact on the region of which are the centers of is the price of corn, while in the case of the region of the development of is the extent of productivity of low class the previous year. The volume of exports of corn in South Sulawesi influenced by the fact that the prices of exported most of the corn and rupiah exchange value.